1994
DOI: 10.1096/fasebj.8.15.8001734
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathway signal tran sduction by the cAMP‐dependent protein kinase

Abstract: Since its discovery a quarter century ago, the cAMP-dependent protein kinase has been a central model for study of the mode of transduction of second messenger signals; more than 300 protein kinases are now known to play keys roles in cellular control. Multiple cellular events are initiated by the activation of the cAMP-dependent protein kinase and correlated with these events has been the identification of a broad spectrum of protein substrates. From model substrates and inhibitors an excellent understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(144 citation statements)
references
References 4 publications
3
137
0
4
Order By: Relevance
“…PKA signaling has been reported to play important roles in multiple physiological processes, including growth, differentiation, gene regulation, and apoptosis (37). Disruption of the PKA catalytic subunit causes destabilization of the diploid cell cycle, and the cells start meiosis under conditions repressive for wild-type meiosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…PKA signaling has been reported to play important roles in multiple physiological processes, including growth, differentiation, gene regulation, and apoptosis (37). Disruption of the PKA catalytic subunit causes destabilization of the diploid cell cycle, and the cells start meiosis under conditions repressive for wild-type meiosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Much, however, remains to be determined about the physiological events of PKA-dependent phosphorylation. With the presence of multiple protein substrates in a single cell, there is a need for not only each substrate to be phosphorylated in response to a cAMP signal, but also for there to be some preference in the order of their phosphorylation and by this means to orchestrate the integration of the cellular response (38). Possibly the existence of multiple catalytic species contributes to such events.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported (Dormond et al, 2002), we found that EP2 and EP4 receptors were expressed in HUVECs and that EP4 was more abound than EP2 (data not shown), suggesting that cAMP may be involved in PGE2-mediated regulation of angiogenesis. The major target molecule of cAMP is PKA, which mediates its effects through phosphorylation of specific substrates (Walsh et al, 1994;Schwartz, 2001). It has also been shown that cAMP can activate the PI3K/Akt pathway (Li et al, 2000), which is involved in the angiogenic process (Walsh and Van Patten, 1994).…”
Section: Pge 2 Stimulates Cell Proliferation Migration and Tube Formentioning
confidence: 99%
“…The major target molecule of cAMP is PKA, which mediates its effects through phosphorylation of specific substrates (Walsh et al, 1994;Schwartz, 2001). It has also been shown that cAMP can activate the PI3K/Akt pathway (Li et al, 2000), which is involved in the angiogenic process (Walsh and Van Patten, 1994). To test whether the angiogenic effect of PGE2 on endothelial cell migration, proliferation, and tube formation would be regulated by the PKA inhibitor PKI and the PI3K inhibitor wortmannin, HUVECs were treated with PGE2 following pretreatment with PKI or wortmannin for 30 min.…”
Section: Pge 2 Stimulates Cell Proliferation Migration and Tube Formentioning
confidence: 99%
See 1 more Smart Citation